Dimeric mimetic of BDNF loop 4 promotes survival of serum-deprived cell through TrkB-dependent apoptosis suppression - L. F. Zainullina (Nature Portfolio, 2021)
Abstract Brain-derived neurotrophic factor (BDNF) is involved in the regulation of neuronal cell growth, differentiation, neuroprotection and synaptic plasticity. Although aberrant BDNF/TrkB signaling is implicated in several neurological, neurodegenerative and psychiatric disorders, neurotrophin-based therapy is challenging and is limited by improper pharmacokinetic properties of BDNF. Dimeric dipeptide compound GSB-106 (bis-(N-monosuccinyl-l-seryl-l-lysine) hexamethylenediamide) has earlier been designed to mimic the TrkB-interaction 4 loop of BDNF. It displayed protective effect in various cell-damaging models in vitro. Animal studies uncovered antidepressive and neuroprotective properties upon GSB-106 per os administration. Current study shows that GSB-106 acts similarly to BDNF, promoting survival of serum-deprived neuronal-like SH-SY5Y cells. 100 nmol concentration of GSB-106 provided maximum neurotrophic effect, which corresponds to about 37% of the maximum effect provided by BDNF. Protective properties of GSB-106 arise from its ability to counteract cell apoptosis via activation of TrkB-dependent pro-survival mechanisms, including inactivation of pro-apoptotic BAD protein and suppression of caspases 9 and 3/7. Thus, our study has characterized neurotrophic activity of small dimeric compound GSB-106, which mimics certain biological functions of BDNF and neurotrophin-specific protective mechanisms. GSB-106 also displays similarities to some known low weight peptide and non-peptide TrkB ligands.